The Miracle Drugs: Hormone Replacement Therapy and Labor Market Behavior of Middle-Aged Women - N. Meltem Daysal; Chiara Orsini (Institute for the Study of Labor (IZA), 2014)
In an aging society, determining which factors contribute to the employment of older individuals is increasingly important. We examine the impact of medical innovations on the employment of middle-aged women focusing on the specific case of Hormone Replacement Therapy (HRT), a common treatment for the alleviation of negative menopausal symptoms. HRT medications were among the most popular prescriptions in the United States until 2002 when the Women's Health Initiative Study the largest randomized control trial on women ever undertaken documented the health risks associated with their long term use. We exploit the release of these findings within a Fixed Effect Instrumental Variable framework to address the endogeneity in HRT use. Our results indicate substantial benefits of HRT use to the short-term employment of middle-aged women.
Keywords: I1; H8; J2; 330; employment; pharmaceutical treatments; Hormone Replacement Therapy